(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The article attempts to examine the nature of interaction that exists among the citizens of India and Uzbekistan which had kept anonymously from the world. The relationship between India and Uzbekistan has been developing continuously since past ancient times they have an exchange of so many cultural and economic core values. This journal article examines how the entrepreneurial spirit, innovative capacity, and adaptability of citizens have been critical to the remarkable economic transformations in India and Uzbekistan. By shedding light on this vital, yet often overlooked, dimension of the India-Uzbekistan relationship, the journal article offers insights into how citizen-led growth can underpin enduring geocultural partnerships.